2020
DOI: 10.1111/appy.12423
|View full text |Cite
|
Sign up to set email alerts
|

Patients' and caregivers' knowledge and beliefs about mental illness in mainland China: A systematic review

Abstract: This review aimed to systematically investigate patients' and caregivers' knowledge and beliefs about mental illness in mainland China. A total of 48 eligible studies (N = 11 895) were retrieved from eight electronic databases. Prevalence statistics were computed for themes (eg, stress) under each construct relating to knowledge or belief about mental illness (eg, beliefs about causes). Effect size r was calculated for each correlation with an identified construct. We found that only 27.8% of patients recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…This study showed that many families had misinterpretations of illness and exhibited some unreasonable behaviors when their children were newly diagnosed with depression, which was consistent with the findings of a recent systematic review. Li and Reavley [36] found that the recognition rate of depression in Chinese mainland family caregivers was low, and they were more likely to regard psychosocial (such as stress) and personality (i.e., introversion) factors as important reasons for mental illness. Because the diagnostic approaches for adolescent depression were mainly based on patient interviews and subjective assessment of their clinical symptoms, it was difficult for parents to believe the diagnosis results from psychiatrists the first time, thus delaying the treatment of the disease [37].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that many families had misinterpretations of illness and exhibited some unreasonable behaviors when their children were newly diagnosed with depression, which was consistent with the findings of a recent systematic review. Li and Reavley [36] found that the recognition rate of depression in Chinese mainland family caregivers was low, and they were more likely to regard psychosocial (such as stress) and personality (i.e., introversion) factors as important reasons for mental illness. Because the diagnostic approaches for adolescent depression were mainly based on patient interviews and subjective assessment of their clinical symptoms, it was difficult for parents to believe the diagnosis results from psychiatrists the first time, thus delaying the treatment of the disease [37].…”
Section: Discussionmentioning
confidence: 99%
“…Both motor and psychosocial dysfunctions and psychiatric comorbidities (eg, bradykinesia, rigidity, gait freezing, depression, fatigue, cognitive decline, and sleep disturbances associated with PD) are common in PD patients, which could lower their QOL. Certain demographic (eg, age, 11,29 gender, 39 education level, 11,63 living condition, 43,64 knowledge and beliefs 64 and marital status 40 ) and clinical characteristics (eg, illness duration, 55 and disease stage, 54‐56 severity 28,42,43 and subtypes 10,53 ) were significantly associated with QOL in PD patients. The findings on the associations between psychiatric comorbidities and QOL in PD are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…The National Health Commission of China also released national guidelines of psychological crisis intervention related to the COVID-19 (Kang et al 2020). Consequently, students' knowledge and better understanding about the COVID-19 epidemic were likely to substantially reduce their uncertainty and fear (Li & Reavley 2021).…”
Section: Discussionmentioning
confidence: 99%